Understanding suicide attempts by adolescent Hispanic females - Zayas, Luis H. et al. (2000)
This article presents integrative model to aid clinicians in understanding suicide attempts by adolescent Hispanic females. On the basis of knowledge accumulated through clinical and research experience, the model describes a convergence of sociocultural, familial, developmental, and psychological factors that include considerations of family and parental functioning; adolescent female development; and the relationships of fathers, mothers, and daughters. - Reproduced
Keywords: Adolescence; Youth; Suicide